Immunological Evaluation of Co‐Assembling a Lipidated Peptide Antigen and Lipophilic Adjuvants: Self‐Adjuvanting Anti‐Breast‐Cancer Vaccine Candidates. (11th August 2020) - Aiga, Taku; Manabe, Yoshiyuki; Ito, Keita; Chang, Tsung‐Che; Kabayama, Kazuya; Ohshima, Shino; Kametani, Yoshie; Miura, Ayane; Furukawa, Hiroto; Inaba, Hiroshi; Matsuura, Kazunori; Fukase, Koichi
Abstract: Co‐assembling vaccines composed of a lipidated HER2‐derived antigenic CH401 peptide and either a lipophilic adjuvant, Pam3 CSK4, α‐GalCer, or lipid A 506, were evaluated as breast cancer vaccine candidates. This vaccine design was aimed to inherit both antigen multivalency and antigen‐specific immunostimulation properties, observed in reported self‐adjuvanting vaccine candidates, by using self‐assembly and adjuvant‐conjugated antigens. Under vaccination concentrations, respective lipophilic adjuvants underwent co‐assembly with lipidated CH401, which boosted the anti‐CH401 IgG and IgM production. In particular, α‐GalCer was responsible for the most significant immune activation. Therefore, the newly developed vaccine design enabled the optimization of adjuvants against the antigenic CH401 peptide in a simple preparatory manner. Overall, the co‐assembling vaccine design opens the door for efficient and practical self‐adjuvanting vaccine development. Abstract : A co‐assembled vaccine, composed of lipidated antigens and lipophilic adjuvants, is reported. This vaccine design possesses both antigen multivalency and antigen‐specific immunostimulation properties, and it induces a robust immune response. This simple vaccine initiated a potent immune response without requiring complex synthesis, allowing efficient and practical development of self‐adjuvanting vaccines.